A representação do Movimento Sufragista na Imprensa Rio-Grandina 1930-1934 - Aguiar, Maria do Carmo Pinto Arana de (2013)
The absence ofdebate on thesuffrage movementin the stateof RioGrande doSulled us toproposethepresentdiscussionand analyzethe representation of thesuffragette movementin the pressof Rio Grande city trough newspaper Echo do Sulbetween the years1930 to 1934. The time frame1930-1934is justifiedfor being apoliticallyturbulent periodin thehistory of RioGrande doSuland Brazil, but especiallyby the intensification ofdemandsfor women's suffragetoits legalizationin the 1934 Constitution. This studyfocuses on thecity of RioGrandewherethere were severalsignificant changes insociety due toincreasingindustrializationthatwascausingchangesin dailycity. These changeswerestillbeing feltin the first decadestwentieth century, whenduring the GreatWarwasthe needofwomen entering thelabor market. Industrializationand contextpermeatedby warforced manywomento joinquicklyfor thepublic space. This insertionin factorieseventuallyaccelerate the formationofmovements forwomen's rights. Theincreased participation of womenin the public sphere, deniedtothembefore, placed themin evidenceat the sametimeallowed theformation ofpoliticizedorganizationswho cameto claimpolitical rights, such as voting.